Cultural Safety as an Outcome of a Dynamic Relational Process: The Experience of Inuit in a Mainstream Residential Addiction Rehabilitation Centre in Southern Canada. (May 2022) - Lauzière, Julie; Fletcher, Christopher; Gaboury, Isabelle
Few addiction treatment options are available in Arctic Canada, leading many Inuit to seek treatment programs in southern cities. We conducted a case study to understand what contributes to a culturally safe experience for Inuit in a mainstream addiction rehabilitation centre in Southern Canada. We carried out more than 700 hours of participant observation, in addition to semi-structured interviews and member-checking activities with 20 Inuit residents, 18 staff and four managers. Data were analysed using an inductive interpretative process. Throughout their journey in the program, Inuit navigated through contrasting situations and feelings that we grouped under six broad themes: having Inuit peers, having limitations imposed on one's ways of being and doing, facing ignorance and misperceptions, having conversations and dialogue, facing language barriers and being in a supportive and caring environment. This study highlights how cultural safety varies according to people, context and time, and relates to developing trustful relationships.